2015
DOI: 10.1111/ijcp.12626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renin-angiotensin system-targeting antihypertensive drugs on treatment of Alzheimer's disease: a meta-analysis

Abstract: Renin-angiotensin system-targeting antihypertensive drugs may be a potential treatment for reducing the incidence and progression of AD. Further studies on RAS-targeting antihypertensive drugs, especially large randomised clinical trials, should be conducted in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…It is noteworthy that angiotensin II itself can contribute to the development of Alzheimer's disease . Despite experimental evidence for a role of ACE in beta‐amyloid clearance, both ARBs and ACE inhibitors have been reported to have favourable effects on beta‐amyloid deposition and cognition, with the effects of ARBs being greater than those of ACE inhibitors . It may therefore not be surprising that the simultaneous inhibition of neprilysin and the angiotensin receptor has not led to the accumulation of pathogenetic forms of amyloid in humans .…”
Section: Safety Of Neprilysin Inhibitionmentioning
confidence: 99%
“…It is noteworthy that angiotensin II itself can contribute to the development of Alzheimer's disease . Despite experimental evidence for a role of ACE in beta‐amyloid clearance, both ARBs and ACE inhibitors have been reported to have favourable effects on beta‐amyloid deposition and cognition, with the effects of ARBs being greater than those of ACE inhibitors . It may therefore not be surprising that the simultaneous inhibition of neprilysin and the angiotensin receptor has not led to the accumulation of pathogenetic forms of amyloid in humans .…”
Section: Safety Of Neprilysin Inhibitionmentioning
confidence: 99%
“…The ten-best combinations of the eleven drugs that excluded drugs acting on the brain and/or psychological level included NSAID, anticoagulant, lipid-lowering, and antihypertensive drugs, as well as estrogen/progestin. Drugs from all of these categories have been shown to reduce AD risk, however they all show disappointing results when used singly in clinical trials [33][34][35][36][37][38][39][40][41][42][43][44][45]. The use of combinations of these and other drugs remains an attractive option [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Recent brain studies of BMS patients with functional magnetic resonance imaging (fMRI) have shown hypofunctional activity in the CNS of patients, especially in the hippocampus and medial prefrontal cortex (Khan, Keaser, Meiller, & Seminowicz, 2014). Because of the discovery that the use of some antihypertensives, such as ARBs, may have a negative association with other CNS pathoses, such as Alzheimer's disease (Ye et al, 2015), we can claim that these medications may play a protective role against neurodegenerative processes linked to ischaemia or reduced function of blood vessels in the brain (Van Agtmaal, Houben, Pouwer, Stehouwer, & Schram, 2017;Direk et al, 2016).…”
Section: Frequency Of Distributionmentioning
confidence: 99%